Efficacy of the rapid maxillary expansion with a modified acrylic splint palatal expander: A randomized clinical trial - Silvia Maria Buratti Corrêa; Luiza Pereira Alves; Murilo Matias; Mayara Paim Patel; Ana Carla Raphaelli Nahás; Liliana Ávila Maltagliati (Arbu Academic Publishing, 2023)
Aim: This prospective randomized clinical trial aimed at analyzing the skeletal effects of this modified acrylic splint palatal expander (MASPE) used for maxillary transversal deficiency treatment in mixed dentition. Methods: Eligibility criteria included maxillary transverse deficiencies in children between 7 and 10 years of age. Eighteen individuals who met the inclusion criteria and reached the end of treatment were evaluated (mean age of 8.66 years old) and randomly assigned to be submitted to rapid maxillary expansion with either the MASPE experimental device or a well-known tooth-borne expander (control group). CBCT scans taken before expansion and at the end of the retention period were evaluated. The palatal area was calculated, and the length of expansion was measured. Treatment changes were analyzed using paired t-tests, whereas independent t-tests were used to compare the two groups. Results: There were statistically significant (p<0.05) increases in maxillary width at the suture level in both groups, with a substantial increase in the palatal area. The group differences were not significant. Conclusions: MASPE showed good efficiency and skeletal effects but no superiority over the control group.